Four dimensions characterize attributions from faces using a representative set of English trait words - Chujun Lin (Nature Portfolio, 2021)
People form impressions about others from seeing their faces, and use many words to describe those impressions. Here, using ratings of 100 representatively sampled white adult faces on a large set of traits, the authors show that trait impressions from faces can be summarized by four psychological dimensions.